2017
DOI: 10.1016/j.theriogenology.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Uterine clinical findings, fertility rate, leucocyte migration, and COX-2 protein levels in the endometrial tissue of susceptible mares treated with platelet-rich plasma before and after AI

Abstract: Persistent mating-induced endometritis (PMIE) results in decreased fertility in horses, thereby causing a significant impact in the horse market. Platelet-rich plasma (PRP), a modulator of the inflammatory response, has been largely used in veterinary medicine. Here, we investigated the effects of PRP on uterine inflammation, conception rate, endometrial polymorphonuclear neutrophil (PMN) migration, and COX-2 protein levels in the endometrial tissue. Thirteen PMIE-susceptible mares were used for artificial ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 51 publications
5
44
1
Order By: Relevance
“…This concurs with another study reporting that PRP decreased endometrial expression of COX-2, decreased PMN numbers in the uterine lumen, and increased pregnancy rates [333]. It has also been shown to act as an anti-inflammatory, and treatment of susceptible mares led to a down-regulation of endometrial IL1β, IL6, and CXCL8 expression [332][333][334][335].…”
Section: Platelet-rich Plasmasupporting
confidence: 90%
See 1 more Smart Citation
“…This concurs with another study reporting that PRP decreased endometrial expression of COX-2, decreased PMN numbers in the uterine lumen, and increased pregnancy rates [333]. It has also been shown to act as an anti-inflammatory, and treatment of susceptible mares led to a down-regulation of endometrial IL1β, IL6, and CXCL8 expression [332][333][334][335].…”
Section: Platelet-rich Plasmasupporting
confidence: 90%
“…For the treatment of endometritis in the horse, one study found that PRP administration at the time of breeding decreased the intrauterine inflammatory response in mares suffering from chronic endometritis, although it did not affect NO production [332]. This concurs with another study reporting that PRP decreased endometrial expression of COX-2, decreased PMN numbers in the uterine lumen, and increased pregnancy rates [333]. It has also been shown to act as an anti-inflammatory, and treatment of susceptible mares led to a down-regulation of endometrial IL1β, IL6, and CXCL8 expression [332][333][334][335].…”
Section: Platelet-rich Plasmasupporting
confidence: 53%
“…Moreover, PRP therapy has attracted attention as an effective therapy for RIF. 14,20,21 Future research issues include investigation of the therapeutic effects of PRP on factors not limited to endometrial thickness, and the precise molecular mechanism of the effect of PRP must be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…More recent use of plasma products has been directed towards immunomodulation rather than elimination of pathogens from the uterus. Platelet Rich Plasma (PRP) was shown to modulate the uterine inflammatory response to semen (Reghini et al 2016, Segabinazzi et al 2017, including mRNA down regulation of pro-inflammatory cytokines and NO in one study (Metcalf et al 2012). The downregulation of NO was initially viewed as promising, since an upregulation of NO-synthase and accumulation of NO in uterine fluid in susceptible mares had been proposed as a possible mechanism for impaired uterine contractility in susceptible mares (Alghamdi et al 2005.…”
Section: Plasmamentioning
confidence: 99%
“…However, subsequent studies could not confirm that PRP caused a consistent downregulation of the gene for NO-synthase or NO (Reghini et al 2016, Troedsson, unpublished observation). Nevertheless, clinical reports have been encouraging, suggesting improved pregnancy rates in mares treated with PRP (Metcalf 2014, Segabinazzi et al 2017. The protocol for treatment with PRP entails separation of 180 mL of whole blood by a special centrifugation system (Angel Cytomedix, Inc.; Gaithersburg, MD), followed by resuspension of the PRP in 10 mL plasma succeeding uterine infusion 24 -36 hours prior to breeding.…”
Section: Plasmamentioning
confidence: 99%